COVID-19 in Indigenous Communities: The Lived Experiences of Extension Educators - Katherine Hartmann (Journal of International Agricultural and Extension Education, 2021)
Cooperative Extension is present in nearly 100% of counties in the United States, but can only be found in a small percentage of Indigenous communities. Much of this inequitable access to educational and agricultural resources can be attributed to the lasting cultural, social, economic, and political effects of settler colonialism in the Land Grant System and the U.S. in general. The COVID-19 pandemic highlighted these inequities, as well as lack of access to traditional foodways, healthcare, and other basic services. Extension educators already working in Indigenous communities were uniquely situated to respond to the crisis and assist the communities they serve in meeting the new challenges. This study explores the lived experiences of some of these educators through qualitative interviews and advocates for their continued and expanded support. For the Land Grant System to live up to its professed mission of access and inclusion, it must provide equitable access to Extension services in Indigenous communities, and the COVID-19 pandemic proved how vital Extension programs are to their development and survival
Keywords: Indigenous communities; COVID-19; settler colonialism; Cooperative Extension.